Sex Steroid-Mediated Control of Oviductal Function in Cattle - Binelli, Mario (Biology (Basel), 2018)
In cattle, the oviduct is a tubular organ that connects the ovary and the uterus. The oviduct lumen stages a dynamic set of cellular and molecular interactions to fulfill the noble role of generating a new individual. Specific anatomical niches along the oviduct lumen provide the appropriate microenvironment for final sperm capacitation, oocyte capture and fertilization, and early embryo development and transport. To accomplish such complex tasks, the oviduct undergoes spatially and temporally-regulated morphological, biochemical, and physiological changes that are associated with endocrine events of the estrous cycle. Specifically, elevated periovulatory concentrations of estradiol (E2) and progesterone (P4) influence gene expression and morphological changes that have been associated positively to fertility in beef cattle. In this review, we explore how E2 and P4 influence oviductal function in the beginning of the estrous cycle, and prepare the oviductal lumen for interactions with gametes and embryos.